Management of preparation of highly qualified decathleters based on the development of a competitive activity model - Tsyplenkova, E. S.; Ogandganov, A. L.; Salamatov, M. B. (Theory and Practice of Physical Culture, 2023)
Objective of the study was to develop a methodology for managing the training of highly qualified decathletes based on creating a model of competitive activity in decathlon.